Optimizing Pistacia lentiscus (mastic tree) food and healthcare applications: phytochemical composition, extraction methods, quality control, and novel delivery systems - Mohamed A. Anwar; Yuting Fu; Haroun Khan; Mohamed A. Farag (Phytochemistry Reviews, 2026)
Pistacia lentiscus , from the Anacardiaceae family, is native to the Mediterranean region and best known for its aromatic resin, Chios mastic gum (CMG), which is exclusively produced on Chios Island, Greece. While the gum is the tree’s primary commercial product, various extracts from different P. lentiscus organs also hold potential applications due to their rich chemical profiles. This review assesses strategies to optimize the utilization of P. lentiscus products, not only the oleogum, in food and healthcare products. First, we review the phytochemical composition and environmental factors affecting this composition, highlighting conditions that maximize yield for different uses and applications. Additionally, various extraction techniques are reviewed, including solvent, ultrasonic-assisted, microwave-assisted, and supercritical fluid extraction methods, to identify the most effective methods. Authentication and quality control aspects, particularly for CMG, are compared, besides highlighting recent advances in novel delivery systems, i.e., liposomes, that are used to enhance the bioavailability of CMG key phytoconstituents. Graphical abstract